Actors, Motivations and Outcomes in the Legislative Process: Policy Influence at Westminster. Issue 1 (17th November 2015) - Russell, Meg; Gover, Daniel; Wollter, Kristina; Benton, Meghan
Abstract : Legislatures in parliamentary systems are frequently seen as weak policy actors, and this is nowhere more true than of the British Westminster parliament. But real-world changes, and recent research, suggest that Westminster's influence is significant and growing. This raises new questions about which non-government actors are influential, and we explore this through analysing 4, 361 amendments proposed to 12 government bills. Assessing non-government amendment 'success' presents challenges, however, since many such proposals are clearly not sincere attempts at legislative change. We thus make two substantive contributions. First, we quantitatively assess the influence of different groups at Westminster, showing both non-government influence and cross-party working to be more extensive than traditionally assumed. Second, we link predictions about opposition and backbench parliamentarians' motivations to the legislative amendment process, proposing a typology of motivations for such amendments, with wider application. Overall, we argue that understanding non-government parliamentarians' diverse motivations shows that they 'fail' far less often than commonly assumed.